2020
DOI: 10.1021/acs.jproteome.0c00380
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Proteomics in Emerging and Re-Emerging Infectious Diseases Caused by RNA Viruses

Abstract: Emerging and re-emerging infectious diseases due to RNA viruses cause major negative consequences for the quality of life, public health, and overall economic development. Most of the RNA viruses causing illnesses in humans are of zoonotic origin. Zoonotic viruses can directly be transferred from animals to humans through adaptation, followed by human-to-human transmission, such as in human immunodeficiency virus (HIV), severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 141 publications
0
20
0
3
Order By: Relevance
“…Recently, global efforts to systematically profile cellular targets of viral proteins have intensified exponentially, greatly expanding the virus–host interaction landscape. Using ectopically expressed viral proteins as baits, multiple studies profiled the interactome of entire viral species including DENV, ZIKV, Ebola or Influenza virus (reviewed in [ 134 ]). For instance, by using label-free LC-MS/MS, multiple independent groups profiled the global cellular interactome of ZIKV in vertebrate and invertebrate cells, identifying cellular proteins with roles in ZIKV-induced neurodevelopmental defects [ 11 , 135 , 136 ].…”
Section: Bottom-up Methodsmentioning
confidence: 99%
“…Recently, global efforts to systematically profile cellular targets of viral proteins have intensified exponentially, greatly expanding the virus–host interaction landscape. Using ectopically expressed viral proteins as baits, multiple studies profiled the interactome of entire viral species including DENV, ZIKV, Ebola or Influenza virus (reviewed in [ 134 ]). For instance, by using label-free LC-MS/MS, multiple independent groups profiled the global cellular interactome of ZIKV in vertebrate and invertebrate cells, identifying cellular proteins with roles in ZIKV-induced neurodevelopmental defects [ 11 , 135 , 136 ].…”
Section: Bottom-up Methodsmentioning
confidence: 99%
“…It should be noted that one of the first proteomic studies on SARS-related proteins was conducted in 2003 and revealed NCAP_SARS protein as a major immunogen [ 25 ]. Interestingly, a caspase cleavage motif (responsible for the virus proteolysis and elimination by the host cells caspases) was present in all previous coronavirus nucleoproteins [ 27 ], but not in SARS-COV-1 [ 25 ]. Dysregulation of PI3K/AKT pathway was identified in both SARS-CoV-2 and SARS-CoV-1 [ 28 ].…”
Section: Main Textmentioning
confidence: 99%
“…Las tecnologías "omicas" inspiradas en el proceso natural de producción de biomoléculas en las células, han aportado significativamente en el avance del diagnóstico, manejo y pronóstico de varias enfermedades, siendo elementales para el perfeccionamiento de la medicina personalizada de próxima generación 180,181 , debido a que permiten una mejor comprensión de los mecanismos moleculares y celulares que interfieren en la progresión de una enfermedad en humanos 180 . Entre las "ómicas" con mayor avance están la genómica, transcriptómica, proteómica y metabolómica 181 , siendo la genómica y proteómica las "omicas", con un protagonismo superior en la investigación de diagnóstico y tratamiento en enfermedades infecciosas 182 . La genómica trata de la estructura, función, evolución y mapeo de genomas, con el objetivo de cuantificar y caracterizar genes 180 .…”
Section: Era De Las "Omicas" Para El Desarrollo De Herramientas Biotecnológicasunclassified
“…La proteómica, por otro lado, estudia todas las proteínas presentes en una célula, tejido u organismo, centrándose en las propiedades bioquímicas, roles funcionales y sus cambios frente al crecimiento o a estímulos internos y externos 182,187,188 . La proteómica a través de espectrometría de masas facilita los análisis de precisión, sensibles y de alto rendimiento de proteínas a gran escala 187 .…”
Section: Era De Las "Omicas" Para El Desarrollo De Herramientas Biotecnológicasunclassified
See 1 more Smart Citation